The bestiary of Camões - Braz, Paulo (2019)
The objective of this paper is a critique of some excerpts from The Lusíadas in which is possible to recognize a manifestation of sacred as an opening to animality’s expression. Georges Bataille’s ideas will be the guide on this research, which equally tries to analyze the dialogues of Camoes’ poetry with the production of some contemporary Portuguese poets.